Entre a cruz e a viola: uma etnografia de práticas devocionais nas Festas de Santa Cruz dos Valos e São Gonçalo - Chaves, Alexandre da Silva (2019)
This thesis aims to present, through qualitative analysis, a feast popularly known as the Feast of the Holy Cross of Valos, that takes place in the city of Franco da Rocha and is considered by devotees a century old celebration. It also presents how the feast devotional practices influence the celebrations in homage to São Gonçalo. The field research uses the techniques of ethnography, thematic life history, and review of sources documentaries, between 2015 and 2018, and focuses on the analysis of the rituals of the Feast and of the Pilgrimage, which is held yearly and whose route goes from an urban neighborhood towards a rural region popularly known as Mato Dentro. On the other hand, religious practices are observed in the celebrations of São Gonçalo, which have no fixed calendar and no location, being performed according to decisions made by payers of promises, devotees and prayers. This thesis dialogues with the classical anthropological literature, especially Rubem Cesar Fernandes (1994), Carlos Alberto Steil (1996) and Carlos Rodrigues Brandão (1981, 2007), all of them authors that study the religious phenomena in urban and rural contexts. In my case, with an ethnography, I approach aspects close to those studied by the authors above mentioned, having the main intention of understanding a set of practices and narratives related to an invented religious tradition which is popularly addressed as a centennial festivity, and analyzing its transmission strategies. It is, therefore, an ethnographic analysis that allows us to understand the dynamics of narrative disputes and how they can transform relations built in their context. In order to understand these transformations, I use the concept of liminality elaborated by Victor Turner (2008; 2013), but applying it in another analytical level